Avaliação alelopática e caracterização fitoquímica do extrato em diclorometano de folhas de Curatella americana L. (Lixeira) - Barbosa, Cecília Soares (2011)
Current methods of controlling weeds have caused a dissatisfaction of social order, for putting at risk the quality of food for human or animal. Faced with this problem, associated with the appearance of more resistant species to current herbicides, it is necessary to find new methods of control. This paper describes a phytotoxic evaluation of diclorometanólico extract of leaves of Curatella americana (lixeira) in order to evaluate their efficiency in relation to the inhibition of seed germination of Panicum maximum (capim-colonião), in boxes Gerbox and greenhouse and the subsequent Panicum maximum characterization of allelopathic compounds responsible for inhibition. Were conducted germination, with a photoperiod of 10 hr for 7 days and with solutions of the extracts at concentrations of 0, 50, 100, 150, 200 and 250 ppm. The extract showed a high potential phytotoxic at concentrations similar to those used by commercial herbicides. In the qualitative identification of secondary metabolites present in the extract diclorometanólico sheet Curatella americana L. identificate flavonoids, anthraquinone aglycones, triterpenes, steroids, polyphenols and tannins. Identification the extract in Cromatography Gas: 3,7,11,15-Tetramethyl-2-hexadecen-1-ol, 2-Hexadeciloxirano; 1-(+)-ascorbic acid2,6-dihexadecanoate, Ethyl-hexadecanoate, and Ethyl-octadecanoate and Tetrapentacontano.